Comparative analysis of 2‐week glycaemic profile of healthy versus mild gestational diabetic pregnant women using flash glucose monitoring system: an observational study. (13th August 2019) - Nigam, A; Sharma, S; Varun, N; Munjal, YP; Prakash, A
Abstract : Objective: To compare glycaemic profiles in women with mild gestational diabetes (GDM) and those with a healthy pregnancy. Design: Observational study. Setting: Hospital‐based. Population: Healthy nonpregnant, healthy pregnant, and women with GDM, diagnosed by oral glucose tolerance test. Methods: Nine nonpregnant women, 33 healthy pregnant women, 29 pregnant women with GDM between 24 and 36 weeks' gestation, received ambulatory glucose profile (AGP) monitoring for a 2‐week period. AGP values were compared in the three groups: 100 days (9600 data points) for nonpregnant women, 396 days (33 792 data points) for healthy pregnant women, and 348 days (34 408 data points) for women with GDM. Results: Mean glucose values for fasting and postmeals were highest in nonpregnant healthy women and lowest in healthy pregnant women ( P  < 0.001). Women with mild GDM had significantly higher blood glucose values than did healthy pregnant women, though still within the target range. Blood glucose values >160 mg/dl were observed in 41.4% (12/29) in the GDM group compared with 18.2% in women with a healthy pregnancy. The maximum peak of day and night time glucose was respectively 234 and 215 mg/dl in women with GDM compared with 183 and 171 mg/dL in the control group. Glycaemic variability as measured by interquartile range was higher in GDM pregnancies. Conclusions: Although the blood glucose level remained within the target levels in women with mild GDM, glycaemic variability and mean blood glucose levels were significantly higher among women with GDM than among women with a healthy pregnancy. Tweetable abstract: Average blood glucose levels and glycaemic variability are significantly higher in women with GDM than in women with a healthy pregnancy. Tweetable abstract: Average blood glucose levels and glycaemic variability are significantly higher in women with GDM than in women with a healthy pregnancy.